Morphological characteristics and motor abilities of boys aged 15 and 17 - Milica Blagojević; Slobodan Ćirak; Borislav Obradović; Filip Sadri; Milorad Jakšić (Exercise and Quality of Life)
Measuring of morphological characteristics and motor abilities was performed on the sample of 51 male students of the secondary traffic school “Pinki” from Novi Sad.  Body height and body mass were used for measuring of morphological characteristics, and results of standing long jump and running at 30 meters with standing start were used for measuring of motor abilities. The body mass index was calculated after the results were obtained. The aims of the study were to establish and analyze differences in the results of morphological status and explosive strength of students measured in different periods, in the first measurement when the subjects were 15 years old and in the second measurement when the subjects were 17 years old. The data obtained in the study were analyzed using repeated measures ANOVA. The obtained results indicate the existence of statistically significant differences between first and second measurement in all morphological characteristics and motor abilities, at the level of significance of p<0.05.A significant increase in morphological characteristics and motor abilities with age, indicating that boys have adequate growth and development for their age.The age factor has a significantly stronger influence than the factor of the curriculum for the physical education in this high school.